Control of brucellosis on an infected Murrah buffalo farm with reduced dose of Brucella abortus S19 vaccine administered by conjunctival route in adult animals - CHAND, PURAN; CHHABRA, RAJESH; JALE, ISHWAR SINGH; BANGER, RAJIV; JANGRA, SUBHASH (The Indian Journal of Animal Sciences, 2013)
Brucellosis caused by Brucella abortus is a serious threat to dairy farming particularly when the area is endemic with no effective vaccination programme. Abortion is the main outcome of brucellosis in pregnant animals with further complication of retention of placenta, reduced milk yield, metritis, temporary or permanent infertility, cost of veterinary services, increased inter-calving period and maintenance of unproductive animal. Owing to abortions, a contaminated environment with a high antigenic load of B. abortus is created on the farm in which vaccination of calves alone is not sufficient to control brucellosis. Vaccination of adult animals including calves would be an effective strategy to control abortions and bring down incidence of the disease. In the present study, attempts were made to control brucellosis on a Murrah buffalo farm where brucellosis entered about 5 years ago, and since then 86 abortions had occurred resulting into colossal losses. The strategy of testing of all animals, segregation of positive population, and decontamination of farm premises coupled with vaccination with B. abortus S19 vaccine of adult buffaloes as well as calves (4–8 months) was adopted. Adult buffaloes were vaccinated with reduced dose of S19 vaccine by conjunctival route and boosted after 4 months while calves were vaccinated by single standard dose of S19 vaccine by subcutaneous route. Only 6.52% (6/ 92) adult buffaloes became serologically positive after 1 month of conjunctival vaccination, however, these animals also became negative after 2 months. The drawback of subcutaneous vaccination of adult animals that they become serologically positive with persistent antibody titres interfering in subsequent testing was circumvented by using the conjunctival route of vaccine administration. Abortions in buffaloes were not recorded after vaccination.